Management of acute peripheral arterial injury by using doppler ultrasonography - Chapagain, D; Reddy, DJ; Chadha, SK; Agarwal, S; Shrestha, KG; Shah, S (Journal of College of Medical Sciences-Nepal, 2013)
Objective To determine the effectiveness of the duplex ultrasonography scanning in the management acute peripheral arterial injury. Materials and methods Its a prospective evaluation comparing duplex scanning with operative exploration finding in 78 patients.Duplex scan was used alone for 98 patients having clinical finding of acute vascular insufficiency. Results Duplex scanning had 100% sensitivity and 95.23% specificity compared with operative exploration in the 78 cases. Duplex scanning detected 78 injuries, 77 of which were confirmed by correlation with operative exploration and 20 patients did not have vascular injury. One false-positive result was due to spasm of the superficial femoral artery. Conclusions Duplex scanning is a noninvasive, safe, effective , rapid and lesion localising method of initial evaluation for acute peripheral vascular injury having clinical features of vascular insufficiency. Journal of College of Medical Sciences-Nepal, 2012, Vol-8, No-3, 36-42 DOI: http://dx.doi.org/10.3126/jcmsn.v8i3.8684